ANALISIS METAKOGNISI SISWA TIPE MELANCHOLIS DALAM MENYELESAIKAN MASALAH MATEMATIKA - Ayu Yarmayani; Silvia Fitriani (Universitas Batanghari Jambi, 2015)
This study aims to describe the student's Metacognition type melancholis in solving math problems. The research results expected useful to optimize the learning activity based on activity of Metacognition in students learning math in the melancholis type, consideration for teachers or schools in drawing up a learning model that fits the research is descriptive qualitative research. Data collection is done by way of an interview based on the troubleshooting task sheet. The subject in this study are students who have a personality melancholis on odd semester academic year 2015/2016.The process of critical thinking can be traced in any troubleshooting steps according to Polya and noted the characteristics of the process of critical thinking which includes stage (1) identification of issues and relevant information, (2) explore the interpretation and connections, (3) alternative to prioritize and communicate conclusions, and (4) integrate, monitor, and filter strategy for handling the reset issue.The results showed that students had indeed melancholis metacognition. Melancholis students can solve given by critical. And the process of critical thinking on solving the problems seen in: phase (1) and (2) the process of Metacognition occurs in step understanding the problem, devise a plan, implement troubleshooting troubleshooting plan and rechecking the results of problem solving. Stage (3) the process of Metacognition occurs in step understanding the problem, devise a plan and carry out troubleshooting troubleshooting plan. (4) the stages of the process of Metacognition occurs in step implement the plan troubleshooting and rechecking the results of problem solving. Based on the results of such studies then the teacher should know the personality and mindset of his protégé participant so that teaching and learning process occurs optimally.Keyword : Metakognisi, Melancholis, and Problem Solving